Effect of propylene glycol addition to the diet of dairy ewes on metabolic profile, milk yield and quality - Chiofalo V. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
To study the effects of propylene glycol on metabolic profile and milk yield and quality during the 30 days prior to and 30 days after lambing, fifty one Valle del Belice dairy ewes were blocked by parity, bodycondition score, previous milk production, and assigned randomly to three groups: Control, Propylene glycol (PG): Low PG: 80 g per ewe per day and High PG: 160 g per ewe per day. During the prepartum period, the addition of 160 g ewe/d of PG caused a decrease (P<0.05) of plasma non-esterified fatty acids, while during the postpartum period propylene glycol increased (P<0.01) plasma glucose. During the prepartum period, plasma total cholesterol and LDL decreased (P<0.01) in ewes of Low PG and High PG groups, while after lambing, plasma urea decreased (P<0.01) in Low PG group. In comparison to control ewes, propylene glycol increased milk yield in Low PG group (+16%) and in High PG group (+25%; P<0.01). The addition of propylene glycol was also associated to a decrease (P<0.01) of milk urea and improved milk clotting time (P<0.05) and curd firmness (P<0.01).
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)